THE DEVELOPMENT OF DIGITAL FLIPBOOK MEDIA IN ENHANCING STUDENTS RELIGIOUS CHARACTER - Kusumaningsih, Mita; Anggriawan Nugroho, Dicky; Syaifuddin, Mohammad; Tarifin, Ahmad (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: In the context of rapid technological advancements and the transition from Industry 4.0 to 5.0, character education faces new challenges. Purpose: To address these, this study develops and tests the effectiveness of digital flipbook media in enhancing the religious character of 10th-grade students at SMK Negeri 1 Warungasem. Method: Using the Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the study assesses the feasibility and impact of the flipbook media. Result: Results from expert evaluations show high feasibility, with media experts rating it at 88%, material experts at 94.29%, and small-scale trials at 97.14%. Large-scale trials also yielded a strong feasibility rating of 90.58%. Pretest and posttest scores revealed significant improvement in students' religious character, with average scores increasing from 51.85 to 78.89. Statistical analysis, including a paired samples t-test (t = 9.113, p = 0.000), confirmed the media’s effectiveness. Conclusion: This study demonstrates that digital flipbook media is a highly effective tool for enhancing students’ religious character, offering an engaging and interactive approach to character education.